Spatial Labour Control: Experiencing Labour Mobility in the Chinese/Asian Restaurant Industry in the United States - Wu, Tommy (Labour / Le Travail, 2024)
This article contributes to understanding the relationship between mobilities and labour control. Focusing on the expansion of the Chinese/Asian restaurant industry in the United States during the last two decades and drawing from a multi-sited, multi-scalar ethnography, the concept of spatial labour control is employed to explicate the various forms of labour control and the mechanisms that contribute to the autogenous reproduction of the industry’s out-of-state work arrangement. Specifically, a spatial lens reveals paternalistic control over workers’ food and housing, spatial control over workers’ morals and affect, and control over workers’ mobilities. Moreover, workers’ constant relocation to new work destinations to combat social isolation and feelings of restlessness unintentionally reproduces the circulation of atomized labour for the industry. Such conditions are inconducive to collectively addressing labour discontent.